Impact of Second Opinions in Breast Cancer Diagnostics and Treatment: A Retrospective Analysis - Heeg, E. (Ann Surg Oncol, 2019)
BACKGROUND: Breast cancer care is becoming increasingly complex, and patients with breast cancer are increasingly aware of the different treatment options, resulting in requests for second opinions (SOs). The current study investigates the impact of breast cancer SOs on final diagnosis and treatment in the Netherlands Cancer Institute (NCI) using a newly designed Breast Cancer Second Opinion (BCSO) classification system. METHODS: Patients who visited the NCI for an SO between October 2015 and September 2016 were included. Demographics, diagnostics, and treatment proposals were compared between first and SO. Discrepancy was categorized using our BCSO classification system, categorizing SOs into (1) noncomparable, (2) identical, and (3) minor or (4) major discrepancy. RESULTS: The majority of SOs (n = 591) were patient initiated (90.7%). A total of 121 patients underwent treatment prior to their SO, leaving 470 patients for assessment of discrepancies according to our BCSO classification system. More than 45% of these SOs resulted in at least one discrepancy, with comparable rates for physician- and patient-initiated SOs (42.5% vs. 45.6%, p = 0.708). Significantly more discrepancies were observed in patients with additional imaging (51.3% vs. 37.2%, p = 0.002) and biopsies (53.7% vs. 40.3%, p = 0.005). Almost 60% of all discrepancies were categorized as major (neoadjuvant systemic treatment instead of primary surgery, breast-conserving surgery instead of mastectomy, and proposing postmastectomy immediate breast reconstruction). CONCLUSIONS: Our findings show substantial differences in diagnostic and treatment options in breast cancer patients visiting the Netherlands Cancer Institute for an SO, thereby emphasizing more consensus for the indications of these treatment modalities.